Prevalence and Antibiotic Sensitivity Pattern of Methicillin- Resistant- Staphylococcus aureus in Kathmandu Medical College -Teaching Hospital - Pandey, S; Raza, MS; Bhatta, CP (Journal of Institute of Medicine Nepal, 2013)
Introduction: Staphylococcus aureus is found to be a major source of community as well as hospital acquired infection. Staphylococcal isolates from tertiary care hospital are found to be resistant to commonly used antimicrobial agents. Methicillin resistant S. aureus (MRSA) with intrinsically developed antimicrobial resistance has been associated with an increase in morbidity and mortality of the patients in the hospital. This study was undertaken to know the antibiotic sensitivity pattern of staphylococcal isolates with special reference to Methicillin resistant S. aureus. Methods: Clinical specimens received from July 2009 to July 2010 in Kathmandu Medical college-Teaching Hospital were processed and all S. aureus isolates were included in the study. The isolates were identified by standard laboratory procedure. The antibiotic susceptibility pattern of all staphylococcal strain was determined by modified Kirby Bauer antibiotic sensitivity method. Results: Of 111 S .aureus isolates 29(26.12%) were identified to be MRSA. The rate of multi drug resistance was 75.86% for MRSA and 6.09% for MSSA. All the staphylococcal isolates were resistant to penicillin. However, all strains were sensitive to vancomycin. Conclusions: This study showed a high prevalence of MRSA in tertiary care hospital of Kathmandu valley. Regular surveillance of hospital-associated infection and monitoring of antibiotic sensitivity pattern is mandatory to reduce MRSA prevalence in hospital and its spread to community as well. Present study conclusively shows that vancomycin remains the first choice of treatment for MRSA infection. To preserve its value, use of vancomycin should be limited to those cases where there are clearly needed. DOI: http://dx.doi.org/10.3126/joim.v34i1.9117 Journal of Institute of Medicine, April, 2012; 34:1 13-17